ADSORPTION BEHAVIOR OF FIBRINOGEN TO SULFONATED POLYETHYLENEOXIDE-GRAFTED POLYURETHANE SURFACES - HAN, DK; RYU, GH; PARK, KD; JEONG, SY; KIM, YH; MIN, BG (TAYLOR & FRANCIS LTD, 1993)
Fibrinogen adsorptions to surface modified polyurethanes (PU, PU-PEO, and PU-PEO-SO3) were studied from plasma in vitro. PU and PU-PEO surfaces demonstrated that initial adsorption increases with increasing plasma concentration in kinetic profiles and adsorption time in adsorption profiles as a function of plasma concentration, but after the plateau is reached, its adsorption amount decreases as plasma concentration (0.2-2.0%) and adsorption time (1-120 min) increase, respectively. In contrast, PU-PEO-SO3 showed that initial adsorption is almost same regardless of plasma concentration and adsorption time, which is due to the high affinity of surface sulfonate group to fibrinogen. All the surfaces indicated the Vroman effect at about 0.6% plasma concentration; however, the displacement was relatively low. Adsorbed amount of fibrinogen at steady state decreased in the order: PU > PU-PEO-SO3 > PU-PEO, regardless of adsorption time and plasma concentration. The adsorption behavior of PU-PEO-SO3 is attributed to both effect of low binding affinity of PEO chain and high affinity of pendant sulfonate group toward fibrinogen.
Keywords: HEPARIN-IMMOBILIZED POLYURETHANES; PLASMA; PEO; INTERFACE; PROTEINS; PLATELET